Implementasi Pengamanan Text File Pada Hybrid Sistem Menggunakan Algoritma Vigenere dan Algoritma Adaptive Minimum Error Least Significant Bit Replacement (AMELSBR) - Wamiliana Wamiliana; Tryo Romadhoni Pujakusuma; Febi Eka Febriansyah; Dwi Sakethi (Jurnal Komputasi, 2018)
The development of technology and the internet allows everyone to exchange data andinformation. Problems arise when the information is confidential, especially for a company,institution and also individuals who have important documents and data. Therefore, the securityof the data is a must. In this case cryptography plays a role of encrypting secret messages intothe form of unreadable messages and steganography that hides the irregular messages into theimage media, resulting in double security in the delivery of secret messages. In this research wedevelop a hybrid system using Vigenere and AMELSBR with cover media in the form of (.jpg)format as input (cover), file type (.png) as output (stegoimage) and data be inserted as a file withtext format. The conclusion of this research is that the hybrid system can be used to encrypt thesecret message and hide it into the cover media to make it more secure in data transmission.Therefore, the use of AMELSBR method is good used in steganography. Stegoimage canwithstand the process of manipulating the brightness and contrast with the image record musthave the dominant black color value (rgb (0,0,0)) or white (rgb (255,255,255)) and not manycolor variants, in other words the image can restore the file without experiencing excessivereduction of meaning after the manipulation of brightness and contrast is an image with binaryimage quality and grayscale image.